Manure in combination with optimal topdressing with nitrogen fertiliser improved growth, grain yields and the efficiencies of water and nitrogen use in winter wheat in the Xinjiang Oasis drylands - Fang,Yanfei; Tang,Jianghua; Zhang,Shanqing; Zhang,Na; Luo,Xiaoying; Hu,Dongping; Xu,Wenxiu (PeerJ, 2025)
Background Currently, low-cost food production using little or no fertiliser is common in oasis dry farming in Xinjiang. This approach results in excessively low crop yields and resource utilisation. Given the limited local precipitation, optimising fertiliser application to improve crop yields, water use efficiency (WUE), and nitrogen use efficiency (NUE) is key. However, the effects of manure and topdressing nitrogen (N) fertiliser on the yields, WUE, and NUE of dryland wheat in the Xinjiang Oasis region of China have not been studied sufficiently. Methods Therefore, we conducted a 2-year field experiment that examined manure (0 and 30 t ha−1 yr−1, expressed with M0, M1, respectively) and topdressing urea (0, 150, and 300 kg ha–1, expressed with N0, N150, N300, respectively) to quantify the effects of different fertilisation strategies on wheat growth and development, crop N uptake (NUA), soil moisture, yields, WUE, and NUE. Results Compared with application of chemical N alone, combination with manure increased leaf area index (LAI) and aboveground biomass (ABG) values, and crop NUA. Soil water storage (SWS) increased with soil depth and was 27.5–55.2% higher in the upper soil layer than in the deeper layer. The high evapotranspiration (ETc) caused by adding manure reduced SWS by promoting crop growth, and increased grain yield, WUE, and NUE by 12.9%, 9.8%, and 29.7%, respectively. Compared to no topdressing N treatment, the N150 and N300 treatments significantly increased LAI values (39.8% and 32.8%), ABG (33.0% and 23.7%), NUA (30.4% and 39.4%), ETc (3.5% and 3.9%), grain yields (16.1% and 10.1%), and WUE (13.7% and 6.8%), while they reduced SWS (8.7% and 9.2%). The interaction effects of manure and nitrogen on LAI, NUA, ETc, and WUE values were significant. The greatest grain yields (2,561.3 and 3,161.2 kg ha−1), WUEs (10.8 and 9.5 kg ha−1 mm−1), and NUEs (32.6% and 43.9%) during the two growing seasons were obtained with the M1N150 treatment. Principal component analysis (PCA) showed that the M1N150 treatment had the highest comprehensive evaluation score. Conclusions Therefore, we suggest that the combination of 30 t ha−1 yr−1 manure and 150 kg ha−1 topdressing N fertiliser is the optimum fertiliser strategy for improving productivity and efficient water and fertiliser management in dryland winter wheat in the Xinjiang Oasis, where precipitation is low.
Keywords: Soil water; Crop productivity; Dryland winter wheat; Manure fertilizer; Topdressing optimization; Water and nitrogen use efficiencies